Víctor Mercader - CO2 and H2O adsorption-desorption cycles for multifunctional Ni-Fe based catalysts in the production of Synthetic Natural Gas - Mercader, Víctor (Jornada de Jóvenes Investigadores del I3A, 2022)
CO2 and H2O adsorption-desorption cycles for multifunctional Ni-Fe based catalysts in the production of Synthetic Natural Gas